Pre and postnatal effect of maternal environmental tobacco smoke exposure on infant's growth parameters - Nada Ziyad Salim; Ban Sahib Diab (Journal of the Pakistan Medical Association, 2024)
Objective: To determine the association between environmental tobacco smoke exposure and growth parameters of infants. Method: The observational, comparative study was done in rural areas of the Al-Karkh sector of Baghdad, Iraq, from December 2021 to March 2022 after approval from the ethics review committee of the College of Dentistry, University of Baghdad, and comprised mothers aged 20-35 years having infants aged up to one year. Those exposed to environmental tobacco smoke were in group A, while non-exposed mothers were in group B. Along with socio-demographic data, a second-hand smoke exposure scale was used. Weight-for-height, height-for-age and weight-for-age indices, as well as head circumference values, were used to measure growth parameters. Data was analysed using SPSS 22. Result: Of the 150 mothers, 67(44.7%) were in group A with mean age 27.8±4.7 years and 83(55.3%) were in group B with mean age 26,1±4.6 years. The mean age of the children was 9.4±3.1 years in group A and 9.2±2.3 years in group B. Husband was the primary source of smoking at home 55(82.08%). When it came to exposure duration, 58(86.57%) had been exposed for years and 9(13.43 %) for months. The mean Z-score for all growth measurements was higher in group B infants compared to group A (p<0.05) except weight-for-height (p>0.05). Conclusion: Mothers’ exposure to environmental tobacco smoke was found to have a significant harmful effect on the growth parameters of infants. Key Words: Pollution, Demography, Dentistry, Smoking,